Managing for quality and performance excellence / James R Evans; William M Lindsay - Evans, James R. (James Robert)1950-
MANAGING FOR QUALITY AND PERFORMANCE EXCELLENCE, 11E helps you learn on your terms. This edition presents the latest developments in the field as you examine fundamental principles, criteria and the historic underpinnings of total quality. The authors provide a solid foundation for understanding and applying technical tools and performance excellence from an enterprise perspective. This digital resource gives you the flexibility to highlight key text, add notes and create custom flashcards. When its time to study, everything that has been flagged or noted can be gathered into an easily accessible guide. The Readspeaker feature reads text aloud, so you can learn on the go, wherever you are.